Determinants of celebrity-owned brands leveraging price premium. Issue 3 (10th July 2017) - Singh, Gaganpreet; Pandey, Neeraj
Abstract : Purpose: The purpose of this paper is to investigate the celebrity-brand association from a different perspective. Design/methodology/approach: This study uses exploratory factor analysis, confirmatory factor analysis, and binary logistic regression. Findings: This study conceptualizes celebrity-owned brands (COBs). It statistically validates the complimentary and synergistic effects of six inter-related but distinct factors that are likely to influence a buyer's willingness to pay price premium for COBs. Originality/value: This study makes a novel attempt by analysing the celebrity-brand relationship from a different perspective. The paper deviates from the traditional and widely researched linkage of a celebrity with a brand through endorsement.